Curcumin reduces oxidative damage by increasing reduced glutathione and preventing membrane permeability transition in isolated brain mitochondria - Jat, D.; Parihar, P.; Kothari, S. C.; Parihar, M. S. (Cellular and Molecular Biology, 2013)
Mitochondria are critical regulators of energy metabolism and programmed cell death pathways. Mitochondria are also the major site for the production of reactive oxygen species which make this organelle more susceptible to oxidative damage and impairments of mitochondrial functions. Antioxidants have been of limited therapeutic success to ameliorate the toxic effects of oxidative stress in mitochondria. One reason may be the inability of mitochondria to selectively take up antioxidants. In the present study we synthesized mitochondrially targeted curcumin with an aim of delivering this polyphenolic compound to isolated mitochondria. Our observations show the strong anti-oxidative effects of curcumin and mitochondrially targeted curcumin against the lipid peroxidation, protein carbonylation and mitochondrial permeability transition induced by tert-butylhydroperoxide. Both curcumin and mitochondrially targeted curcumin significantly enhanced endogenous reduced glutathione level in the mitochondria thus preserving mitochondrial defense system against oxidative stress. We concluded that curcumin and mitochondrially targeted curcumin protected mitochondria against tert-butylhydroperoxide by lowering the oxidative damage, increasing the availability of endogenous reduced glutathione and preserving the mitochondrial integrity. Importantly, mitochondrially targeted curcumin was found most effective in ameliorating oxidative stress and preserving mitochondrial integrity than curcumin.